2022
DOI: 10.1038/s41598-022-14638-4
|View full text |Cite
|
Sign up to set email alerts
|

Using fluorescent promoter-reporters to study sugar utilization control in Bifidobacterium longum NCC 2705

Abstract: Bifidobacteria are amongst the first bacteria to colonize the human gastro-intestinal system and have been proposed to play a crucial role in the development of the infant gut since their absence is correlated to the development of diseases later in life. Bifidobacteria have the capacity to metabolize a diverse range of (complex) carbohydrates, reflecting their adaptation to the lower gastro-intestinal tract. Detailed understanding of carbohydrate metabolism regulation in this genus is of prime importance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Bifidobacteria are believed to play an important role in carbohydrate fermentation in the colon. They can indeed ferment various complex carbon sources, such as gastric mucin, xylo-oligosaccharides, (trans)-galactooligosaccharides, soybean oligosaccharides, malto-oligosaccharides, fructooligosaccharides, pectin, and other plant derived-oligosaccharides, although the ability to metabolize carbohydrates is species-and strain-dependent and via bifid-shunt such have been reported in Bifidobacterium NCC2705 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacteria are believed to play an important role in carbohydrate fermentation in the colon. They can indeed ferment various complex carbon sources, such as gastric mucin, xylo-oligosaccharides, (trans)-galactooligosaccharides, soybean oligosaccharides, malto-oligosaccharides, fructooligosaccharides, pectin, and other plant derived-oligosaccharides, although the ability to metabolize carbohydrates is species-and strain-dependent and via bifid-shunt such have been reported in Bifidobacterium NCC2705 [34].…”
Section: Discussionmentioning
confidence: 99%
“…For example, glucose was demonstrated in B. longum to repress the production of Frk , a fructokinase required for the catabolism of fructose [ 17 ]. Recently, we demonstrated that glucose and galactose are sequentially metabolized in B. longum NCC 2705 and that the presence of residual glucose inhibited the consumption of galactose in that strain [ 18 ]. In B. lactis , glucose was shown to repress the expression of sucrose utilization genes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%